Seasonal carbon dynamics and the effects of manure application on carbon budget of a managed grassland in a temperate, humid region in Japan. (17th February 2014) - Matsuura, Shoji; Miyata, Akira; Mano, Masayoshi; Hojito, Masayuki; Mori, Akinori; Kano, Shunpei; Sasaki, Hiroyuki; Kohyama, Kazunori; Hatano, Ryusuke
Abstract We conducted a field experiment from 2004 to 2007 in a temperate, humid region in Japan to investigate seasonal carbon dynamics and their interaction with vegetation. We also examined the effect of composted livestock manure application on the carbon budget in an intensively managed grassland. Two experimental plots were established for the study: one receiving only chemical fertilizer and the other receiving composted cattle manure and supplementary chemical fertilizer. Carbon dioxide flux was measured continuously using the eddy covariance technique, and net ecosystem production (NEP) and net biome production (NBP) were evaluated. We found that the seasonal variations of carbon dynamics were affected not only by climatic conditions but also by vegetation. NEP during the first crop increased rapidly to a high value, which resulted in positive cumulative NEP. In contrast, cumulative NEP during the second to the fourth crop and during winter was only slightly positive or even negative. Thus, NEP during the first crop made a significant contribution to annual NEP. It also occupied an important place in annual NBP via carbon stock into the belowground biomass. The different fertilization regimes between the plots resulted in no significant differences in harvest or NEP on an annual basis. However, the chemically fertilized grassland plot lost carbon, whereas the plot receiving composted cattle manure and supplementary chemical fertilizer accumulated carbon. These results suggest that manure application results in sustainable grassland management enhancing carbon sequestration.